Metodologija za ocene potencialov lesa v Sloveniji - Ščap, Špela (Acta silvae et ligni, 2014)
The information on wooden potentials from Slovenian forests is important for all stakeholders involved in the forest-wood chain (such as enterprises engaged in purchasing, processing or sales of roundwood, pulp industry, CHP plants ...). For these stakeholders, the actual amounts of wood appearing on the market are relevant. Thus the amount of wood consumed by forest owners for their own needs should be excluded. The Slovenian Forestry Institute has developed its own methodology for the evaluation of the actual and theoretical estimates of the quantities of timber. This article presents the potentials of both coniferous and deciduous roundwood as well as wood of lower quality. The actual potentials are based on the five-year averages (2009-2013) of wood that had previously been marked by district foresters for harvesting and at that time appeared on the market. The theoretical potentials, on the other hand, delineate the maximum amount of wood that can be harvested annually and sold on the market, while providing for sustainable forest management at the same time. The results are given in net cubic metres (m3 without bark) and oven-dry tons (ODT) when dealing with energy potential of lower-quality wood. The results show that in the case of spruce and fir trees the actual net quantity of roundwood on the market amounts to 1,239,000 m3. The assessment of theoretically marketable potentials of deciduous roundwood is 410,000 m3, while the actual amount of the deciduous roundwood on the market is 206,000 m3. In the case of lower-quality wood, the assessment of the total theoretically marketable potential is 1,443,000 ODT, while the assessment of the actual potentials on the market amounts to 468,000 ODT. The results indicate a low utilization rate of Slovenian forests, especially as far as privately owned forests are concerned. Still, we should be cautious in interpreting the results, as the analyses of the actual potential consider only the timber that was marked for harvesting by district forester, while in reality the harvested quantities are likely to be greater especially in privately owned forests.
Keywords: modeli; okrogli les; količine lesa; trg; hlodi; les slabše kakovosti; kakovovst lesa; Slovenia; Slovenija